Making sense of nature representation, politics and democracy - Castree, Noel 1968- (Routledge, 2014)
"We listen to a cacophony of voices instructing us how to think and feel about nature, including our own bodies. The news media, wildlife documentaries, science magazines, and environmental NGOs are among those clamouring for our attention. But are we empowered by all this knowledge or is our dependence on various epistemic communities allowing our thoughts, sentiments and activities to be unduly governed by others? Drawing on over 30 years on research into the 'social constitution of nature', Making Sense of Nature shows that what we call 'nature' is made sense of for us in ways that make it central to social order, social change and social dissent. By utilising insights and extended examples from anthropology, cultural studies, human geography, philosophy, politics, sociology, science studies, this interdisciplinary text asks whether we can better make sense of nature for ourselves, and thus participate more meaningfully in momentous decisions about the future of life - human and non-human - on the planet. This book shows how 'nature' can be made sense of without presuming its naturalness. The challenge is not so much to rid ourselves of the idea of nature and its 'collateral concepts' (such as genes) but instead, we need to be more alert to how, why and with what effects ideas about 'nature' get fashioned and deployed in specific situations"--Provided by publisher.